Glucose Tolerance in Pregnant Women Inflicted with Candida Albicans - AL-Khayat, Tarik Hovthy A.T.; AL-Mulla, Fatma Haider K. (AL-Kindy College Medical Journal, 2009)
Background: Many previous studies were concerned with the relationship between gestational diabetes and the development of vaginal candidiasis in pregnant women. In this study, our aim is directed to uncover glucose tolerance status in non-diabetic pregnant women inflicted with candida albicans. Methods: Thirty-four pregnant women with vaginal condidiasis (as demonstrated by microscopy) were enrolled in this study. The patients were nearly similar in their anthropometric and demographic criteria with those of the healthy pregnant women (control group, forty –two women). Fasting plasma sugar and glucose tolerance test were alone for all patients and control group. Results: fasting plasma sugar was significantly higher in the candidiasis-positive pregnant women in comparison to those of candidiasis-negative subjects (5.09 mmol/L vs. 4.71, p <0.02). Plasma glucose level after 30 minutes of performing oral glucose tolerance test was also significant (8.47mmol/Lvs. 7.84, P <0.04). The same trend of significance was noticed after 60 minutes and 120 minutes of performing the corresponding test. The results were (8.13 mmol/L vs. 7.10, P <0.02) and (6.90mmol/L vs. 6.15, P<0.05) respectively. Conclusion: the results reveal an impaired oral glucose tolerance test in pregnant women with candida albicans